2018
DOI: 10.1186/s13018-018-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on the healing of bone fracture in mice

Abstract: BackgroundObesity affects bone health to varying degrees, depending on the skeletal site (weight-bearing or non-weight-bearing) and compartment (cortical or trabecular), and is a risk factor for orthopedic disorders, including bone fractures. However, the effect and mechanisms of obesity on healing of bone fracture is little understood.MethodsThe healing bone fractures of the tibia in genetically obese mice was evaluated relative to normal mice at weekly intervals for 28 days using X-ray scans, hematoxylin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…Some authors hold that fat tissue can exert osteoprotective influences [25][26][27]. In contrast, other researchers document that overweight or obesity impede bone growth and development [28,29], or simply accelerate osteoresorption [30,31]. In the current study, it was observed that the dietary-induced obesity (DIO) in adult females (SHO-FAT group) lowered BMC and BMD in relation to SHO females treated with the control diet (SHO-CON).…”
Section: Discussionmentioning
confidence: 53%
“…Some authors hold that fat tissue can exert osteoprotective influences [25][26][27]. In contrast, other researchers document that overweight or obesity impede bone growth and development [28,29], or simply accelerate osteoresorption [30,31]. In the current study, it was observed that the dietary-induced obesity (DIO) in adult females (SHO-FAT group) lowered BMC and BMD in relation to SHO females treated with the control diet (SHO-CON).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, obesity significantly limited fracture repair, with no callus or connected bone observed in obese mice days after fracture unlike control animals. 81 High levels of limb fractures are also observed in obese children, [82][83][84] where abnormal BMAT and adiponectin levels may be contributing to reduced bone strengthen and delayed repair.…”
Section: Role Of Adiponectin In the Regulation Of Bone Homeostasismentioning
confidence: 99%
“…X-ray and CT scan X-ray examination and CT examination analysis have been widely used to assess fracture healing. The right femur X-ray image was taken on days 7, 14, and 21 following the procedure using the Faxitron system (Faxitron X-ray, Wheeling, IL, USA) [24,25]. The right femur was examined using a Viva CT 40…”
Section: Tissue Preparationmentioning
confidence: 99%